Comparison of CA-125, conventional ultrasound and CT imaging in diagnosis and staging of ovarian cancer correlated with surgico-pathological findings - Moideen, Nilufer; Hebbar, Shripad S.; Rai, Lavanya; Guruvare, Shyamala; Adiga, Prashant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preoperative evaluation of suspected ovarian malignancy is of paramount importance and a diagnostic tool with high degree of precision helps treating physician in planning appropriate surgery and also neoadjuvant chemo therapy in candidates who are not currently fit for extensive surgical procedure. Though the ultrasound examination of abdomen and pelvis helps one in detection and characterization of adnexal lesion to some extent, its diagnostic ability is further improved by addition of advanced imaging techniques such as computed tomography, magnetic resonance imaging and thus can prove beneficial in choosing patient for right surgery, there by optimising the treatment outcome. Objective of current study was to compare ultrasonography imaging, CT imaging, CA-125 values, RMI 3 score, surgical staging and histopathological findings in carcinoma ovary. Methods: The study is a prospective observational study, carried out between September 2011 and July 2013, in the department of obstetrics and gynaecology, Kasturba hospital, Manipal. All cases of carcinoma ovary who underwent imaging (USG, CT/ MRI) were followed by staging laparotomy during the course of study. All cases of carcinoma ovary who has undergone neoadjuvant chemotherapy were excluded. All patients included in the study underwent CA-125 estimation, conventional ultrasound, CT scan (Sixty four slice with contrast) followed by staging laparotomy and histopathological examination of the specimen. RMI-3 (Risk Malignancy Index Score-3) was calculated in all cases. Results: 54 patients were included in the evaluation. The efficacy of CT (Sensitivity 95.1%, specificity 46.2%) and Ultrasound (Sensitivity 90.2%, specificity 53.8%) were comparable in detection of ovarian malignancy. Combination of CT and USG (Sensitivity 95%, specificity 78.6%) gave the best result in non-invasive investigations whereas combination of CT and surgical staging (Sensitivity 95.1%, specificity 84.6%) gave a better result when invasive modalities were considered. RMI-3 score had sensitivity of 82% and specificity of 64% and did not improve the accuracy. Conclusions: Optimal preoperative evaluation was achieved with combination of USG and CT. Additional of CA-125 further improved the precision. All the three modes had good diagnostic performances, and complimented each other in further refining the characterization of the mass, local spread and distant tumour dissemination.